PENGARUH MODEL LEARNING CYCLE 5E TERHADAP HASILBELAJAR SISWA PADA MATERI LAJU REAKSI - Susanto, Ary; Masriani, Masriani; Sartika, Rody Putra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract: the objective of this study were to determine of differences in learning outcomes and how great the students’ influence taught using learning cycle model and conventional model in reaction rate material toward students of class XII at SMK Negeri 2 Pontianak. The type of this study was quasy experimental design with nonequivalent control group design. The population this study was from all student of XII at SMK Negeri 2 Pontianak, they were XII TOI, XII TPPPP, XII TEI, and XII TKR. Random sampling is used in this study with class XII TPPPP as the experiment class and class XII TEI as the control class. The tools of data collecting was the test learning outcomes. The results of this study showed that the learning outcomes of the experiment class with the control class with value sig. 0,000 < 0,05 meant there were differences between learning outcomes from the control class that used conventional learning and the experiment class that use,.d learning cycle 5E. Learning cycle 5E influenced about 41,15% with effect size 1,03 included in high category against the learning outcomes in reaction rate material toward students of class XII at SMK Negeri 2 Pontianak.Keywords: Learning cycle 5E model, learning outcome, reaction rate